Industrial microwave heating - Metaxas, A. C.; Meredith, R. J. (Roger J.) (Institution of Engineering and Technology, 1988)
The book has 11 chapters and the following topics are dealt with: dielectric loss; dielectric properties; volumetric heating; travelling wave applicators; multimode oven applicators; single mode resonant cavities; special applicator structures; microwave heating circuit; breakdown phenomena; vacuum processing; hazards, leakage & safety; and industrial applications and economics.